The expected and the unexpected in recovery and development after abuse and neglect: The role of early foster carer commitment on young children's symptoms of attachment disorders and mental health problems over time. (May 2022) - Turner, Fiona; Venturini, Enrico; Kainth, Gary; Crawford, Karen; O'Connor, Rory; Balestrieri, Matteo; MacDonald, Sara; Minnis, Helen
Abstract: Background: Whilst we know that foster care is better than institutional care for abused and neglected children, we know less about the specific qualities of foster care that are important for their development and recovery from maltreatment effects. Objective: This is the first study to investigate the effects of foster carer commitment on symptoms of Attachment Disorders (AD) and mental health problems in young children post-maltreatment. Participants & setting: 144 children, age 0–5, recently accommodated into foster care as part of an ongoing Randomised Controlled Trial. Methods: Children were assessed using the Disturbances of Attachment Interview and the Strengths and Difficulties Questionnaire, then followed up 15 months and 2.5 years thereafter. Commitment of the foster carer was measured by 'This Is My Baby' interview. Multiple regression was used to analyse the data. Results: Higher initial foster carer commitment, measured shortly after entry to care, was associated with a reduction in Reactive Attachment Disorder symptoms 15 months after placement, with a modest (non-significant) association persisting 2.5 years later. Initial commitment was not associated with symptoms of Disinhibited Social Engagement Disorder at any follow-up time point, nor with symptoms of mental health problems at 15 months. However, higher initial commitment was unexpectedly associated with higher mental health symptom scores at 2.5 years post-accommodation. Conclusions: This study highlights the complex and non-linear development of children in committed foster care, underscoring the need to examine multiple time-points and to consider symptoms of Attachment Disorders separately from those of other mental health problems.